Creating Canadian English : the professor, the mountaineer, and a national variety of English - Dollinger, Stefan (Newyork: CambridegeUty press, 2019)
"This lively account of the making of Canadian English traces the variety's conceptual, social and linguistic developments from the twentieth century to the present. This book is not just another history of Canadian English; it is a history of the variety's discovery, codification, and eventual acceptance, as well as the contribution of the linguists behind it. Written by an active research linguist focusing on Canadian English, this book is an archive-based biography on multiple levels. Through a combination of new data and re-interpretations of existing studies, a new voice is given to earlier generations of Canadian linguists who, generally forgotten today, shaped the variety and how we think about it. Exploring topics such as linguistic description and codification, dictionary making, linguistic imperialism, linguistic attitudes, language and Canadian identity, or the threat of Americanisation, Dollinger presents a coherent, integrated and balanced account of developments spanning over almost a century"--
"This lively account of the making of Canadian English traces the variety's conceptual, social and linguistic developments from the 20th century to the present. This book is not just another history of Canadian English; it is a history of the variety's discovery, codification, and eventual acceptance, as well as the contribution of the linguists behind it. Written by an active research linguist focussing on Canadian English, this book is an archive-based biography on multiple levels. Through a combination of new data and reinterpretations of existing studies, a new voice is given to earlier generations of Canadian linguists who, generally forgotten today, shaped the variety and how we think about it. Exploring topics such as linguistic description and codification, dictionary making, linguistic imperialism, linguistic attitudes, language and Canadian identity, or the threat of Americanisation, Dollinger presents a coherent, integrated and balanced account of developments spanning over almost a century"--
Machine generated contents note: 1. What is Canadian English?; 2. The heritage of Canadian English; 3. Avis pulls it off; 4. The 'technology': slips, slips, and more slips; 5. 1967 - excitement and hype; 6. Riding the wave of success; 7. A global village and a national dictionary war; 8. Decolonizing DCHP-1 and DCHP-2; 9. Is there really a Canadian English?; Further reading.
Includes bibliographical references and index.
Keywords: English language -- Canada; English language -- Canada; English language -- Canada